2018
DOI: 10.3329/jbcps.v36i1.35505
|View full text |Cite
|
Sign up to set email alerts
|

Oral Azithromycin Pulse Therapy and Daily Topical Benzoyl Peroxide in the Treatment of Acne Vulgaris: An Open Clinical Trial Study

Abstract: Introduction: Combination therapy is an effective approach to simultaneously target multiple pathogenic factor of acne. A unique combination of oral azithromycin pulse therapy and daily topical benzoyl peroxide has been developed for treatment of acne.Material & Methods: It was an open, controlled, clinical trial, conducted on 37 out patients with acne vulgaris. Patients were clinically assessed at baseline &at week 0,4, 8 and 12. Evaluation included success rate (subjects clear or excellent improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…They have shown a 70.7% reduction in Michaelsson Acne Severity Index after 8 weeks (which is almost similar to our results) and an 87% reduction in lesions after 12 weeks. 37 The efficacy of Azithromycin pulse therapy (Azithromycin 500mg thrice weekly) was also established by Sharma et al, in 8 weeks study on 200 subjects having moderate to severe acne (19-38 GAGS score) with total efficacy of 75%, which could be attributed to bigger sample size. 38 On analysis of pre-treatment and post-treatment safety parameters, it was observed that there was no significant change in any of the parameters in both the groups as summarized in table 3.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…They have shown a 70.7% reduction in Michaelsson Acne Severity Index after 8 weeks (which is almost similar to our results) and an 87% reduction in lesions after 12 weeks. 37 The efficacy of Azithromycin pulse therapy (Azithromycin 500mg thrice weekly) was also established by Sharma et al, in 8 weeks study on 200 subjects having moderate to severe acne (19-38 GAGS score) with total efficacy of 75%, which could be attributed to bigger sample size. 38 On analysis of pre-treatment and post-treatment safety parameters, it was observed that there was no significant change in any of the parameters in both the groups as summarized in table 3.…”
Section: Discussionmentioning
confidence: 88%
“…Subjects of both genders, belonging to the 13 to 35 years age group and willing to sign the informed consent form with moderate to severe acne (GAGS score [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] were included. Pregnant and lactating women, patients suffering from PCOD or using hormonal contraceptives were excluded.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%